Best Practices in Recruitment and Outreach to Women and Diverse Veterans for Coronavirus Research at the U.S. Department of Veterans Affairs - Collaboration group; Collaboration group (Mary Ann Liebert, 2023)
In September 2020, the Department of Veterans Affairs (VA) launched a novel volunteer research registry to rapidly recruit eligible study participants for research on SARS-CoV-2 and COVID-19 vaccines and treatments at VA Medical Centers selected as study sites for COVID-19 clinical trials. Targeted multimedia outreach campaigns were used to recruit diverse populations, including those historically under-represented in medical research. By November 2022, 58,561 volunteers were enrolled in the registry, 19% of whom were women, 9% Hispanic/Latino, and 8% Black. The registry's strategic approach to outreach proved successful in recruiting diverse volunteers, with geotargeted e-mails recruiting the most diversity.